Pengaruh Profitabilitas, Likuiditas dan Struktur Modal terhadap Net Profit Margin pada Perusahaan Sektor Financial yang Terdaftar di Bursa Efek Indonesia - Febrianti, Widya; Mursalin, Mursalin; Darmawati, Tri (Budgeting: Jurnal Akuntansi Syariah, 2025)
The aim of this research is to analyze the effect of profitability, liquidity, and capital structure on Net Profit Margin. This present research applies a quantitative approach. 19 companies from the insurance subsector listed on the IDX are include in the study sample. The This Purposive Sampling method is utilized in this research to select data samples through predetermined criteria so that 9 companies with a total data sample of 36 are obtained. The literature study and documentation technique applied in this study were used to collect data. This study data analysis techniques include the use of IBM SPSS 26 software, consisting of descriptive statistics, classical assumption test, multiple regression analysis, coefficient of determination, t-test, and F-test. Partial examination results indicate that Net Profit Margin is significantly impacted by profitability (ROA) as much as 0.001 < 0.05 and liquidity (CR) significantly affect the net profit margin as much as 0.012 < 0.05, while capital structure (DER) affects NPM significantly using a significance the worth of 0.011 < 0.05. Having significance level of 0.00 < 0.05, Profitability (ROA), liquidity (CR) and capital structure (DER) all have an affect net profit margin simultaneously.